2017
DOI: 10.1523/jneurosci.1698-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Large Soluble Oligomers of Amyloid β-Protein from Alzheimer Brain Are Far Less Neuroactive Than the Smaller Oligomers to Which They Dissociate

Abstract: Soluble oligomers of amyloid ␤-protein (oA␤) isolated from the brains of Alzheimer's disease (AD) patients have been shown experimentally (in the absence of amyloid plaques) to impair hippocampal synaptic plasticity, decrease synapses, induce tau hyperphosphorylation and neuritic dystrophy, activate microglial inflammation, and impair memory in normal adult rodents. Nevertheless, there has been controversy about what types of oligomers actually confer these AD-like phenotypes. Here, we show that the vast major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
119
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(133 citation statements)
references
References 2 publications
13
119
1
Order By: Relevance
“…The concentration of AβOs in cerebral cortex brain tissue isolated from controls or from AD patients varies from 50 nM to 2 μM (Yang et al, 2017). We used the sub-lethal AβOs concentration of 500 nM, which is deleterious to neuronal function because it inhibits long term potentiation (Wang et al, 2002; Schlenzig et al, 2012) and produces aberrations in synapse composition, shape and density (Lacor et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of AβOs in cerebral cortex brain tissue isolated from controls or from AD patients varies from 50 nM to 2 μM (Yang et al, 2017). We used the sub-lethal AβOs concentration of 500 nM, which is deleterious to neuronal function because it inhibits long term potentiation (Wang et al, 2002; Schlenzig et al, 2012) and produces aberrations in synapse composition, shape and density (Lacor et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that under certain circumstances in human AD cortex, highmolecular-weight Aβ species dissociate into small neurotoxic oligomeric Aβ species, and administration of the latter to mice activates microglia in vivo. These activated microglia were characterized by increased microglial CD68 levels and decreased ramification (72). In vitro, Aβ activates microglia by binding to PRRs, including receptors for advanced glycation end products (RAGE) (73), TLRs (74), and scavenger receptors (75,76).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…If such soluble forms of Aβ are indeed crucial for the local circuit dysfunctions, then their reintroduction into APP23xPS45 mice that had been successfully treated with NB-360 should lead to a reemergence of neuronal hyperactivity. Plaques are dimer-rich, and dimers (the smallest Aβ oligomers) are thought to be the principal "cytotoxins" in the AD brain (20,21). Therefore, we superfused the cortex of NB-360-treated APP23xPS45 mice with synthetic Aβ dimers (21), after which hyperactivity recurred (Fig.…”
Section: Significancementioning
confidence: 99%